Aortic valve stenosis and aortic diameters determine the extent of increased wall shear stress in bicuspid aortic valve disease. Issue 2 (16th February 2018) - Farag, Emile S.; van Ooij, Pim; Planken, R. Nils; Dukker, Kayleigh C.P.; de Heer, Frederiek; Bouma, Berto J.; Robbers‐Visser, Danielle; Groenink, Maarten; Nederveen, Aart J.; de Mol, Bas A.J.M.; Kluin, Jolanda; Boekholdt, S. Matthijs
Abstract : Background: Use of 4‐dimensional flow magnetic resonance imaging (4D‐flow MRI) derived wall shear stress (WSS) heat maps enables identification of regions in the ascending aorta with increased WSS. These regions are subject to dysregulation of the extracellular matrix and elastic fiber degeneration, which is associated with aortic dilatation and dissection. Purpose: To evaluate the effect of the presence of aortic valve stenosis and the aortic diameter on the peak WSS and surface area of increased WSS in the ascending aorta. Study Type: Prospective. Subjects: In all, 48 bicuspid aortic valve (BAV) patients (38.1 ± 12.4 years) and 25 age‐ and gender‐matched healthy individuals. Field Strength/Sequence: Time‐resolved 3D phase contrast MRI with three‐directional velocity encoding at 3.0T. Assessment: Peak systolic velocity, WSS, and aortic diameters were assessed in the ascending aorta and 3D heat maps were used to identify regions with elevated WSS. Statistical Tests: Comparisons between groups were performed by t ‐tests. Correlations were investigated by univariate and multivariate regression analysis. Results: Elevated WSS was present in 15 ± 11% (range; 1–35%) of the surface area of the ascending aorta of BAV patients with aortic valve stenosis (AS) ( n  = 10) and in 6 ± 8% (range; 0–31%) of the ascending aorta of BAV patients without AS ( P  = 0.005). The mid‐ascending aortic diameter negatively correlated with the peak ascending aortic WSS (R = –0.413, P  = 0.004) and the surface area of elevated WSS (R = –0.419, P  = 0.003). Multivariate linear regression analysis yielded that the height of peak WSS and the amount of elevated WSS depended individually on the presence of aortic valve stenosis and the diameter of the ascending aorta. Data Conclusion: The extent of increased WSS in the ascending aorta of BAV patients depends on the presence of aortic valve stenosis and aortic dilatation and is most pronounced in the presence of AS and a nondilated ascending aorta. Level of Evidence: 2 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2018;48:522–530.